PENGARUH FEE AUDIT, AUDIT TENURE, DAN REPUTASI KAP TERHADAP KUALITAS AUDIT - Fania Azzahroh (2022)
The purpose of this study is to examine the effect of the fee audit fee, audit tenure, and accounting firm reputation on audit quality. This research used quantitative research method. This data collected was secondary data by documentation and literature study. The sample used in this study was manufacturing sector companies listed on the Indonesia Stock Exchange in 2018-2020. The sample of this study amounted to 213 observational data from 71 companies selected by purposive sampling method. The test tool used in this study using SPSS version 24. The data analysis technique used is logistic regression analysis with a 5% significance level. According to the findings of this study, (1) fee audit has no significant effect on audit quality, (2) audit tenure has no significant effect on audit quality, and (3) accounting firm reputation reputation has no significant effect on audit quality.